Coronavirus (SARS-CoV-2): Preventions, keys to diagnosis and treatment of SARS-CoV-2 - Kuldeep Singh Patel (Emergency Department of Hospital San Pedro (Logroño, Spain), 2020)
World Health Organization (WHO) is gathering the latest scientific findings and knowledge on coronavirus disease (SARS-CoV-2) and compiling it in a database. WHO update the database daily from searches of bibliographic databases, hand searches of the table of contents of relevant journals, and the addition of other relevant scientific articles that come to our attention. The entries in the database may not be exhaustive and new research will be added regularly. Nobel coronavirus investigators, the recognition of a nobel coronavirus as the cause of severe acute respiratory syndrome (SARS) was certainly remarkable, yet perhaps not surprising. Advances in the biology of coronaviruses have resulted in greater understanding of their capacity for adaptation to new environments, transspecies infection, and emergence of new diseases. New tools of cell and molecular biology have led to increased understanding of intracellular replication and viral cell biology, and the advent in the past five years of reverse genetic approaches to study coronaviruses has made it possible to begin to define the determinants of viral replication, transpecies adaptation, and human disease. This summary will discuss the basic life cycle and replication of the well-studied coronavirus, mouse hepatitis virus (MHV), identifying the unique characteristics of coronavirus biology and highlighting critical points where research has made significant advances, and which might represent targets for antivirals or vaccines. Areas where rapid progress has been made in SCoV research will be described. Finally, areas of need for research in coronavirus replication, genetics, and pathogenesis will be summarized.